Neglected Agents and the Cultural Nexus of Power within Protestant Churches and Associated Institutions in the Latter Half of the Twentieth Century in Hong Kong - Chen, Haocheng (2024)
In the latter half of the twentieth century, Protestant churches in Hong Kong and institutions associated with them played a significant role in the daily lives of the people of Hong Kong. However, the role of ordinary people in the social functions of Protestant churches in Hong Kong during this period has rarely been explored in the previous literature. Interpreting several cases from written archives and oral history archives, this study aims to demonstrate how Protestant churches in Hong Kong held special significance as a public place for the ordinary people of the local community, who played an active role in these churches to serve the local community and derived self-satisfaction from doing so. This study also reveals how these local Protestant churches and the associated institutions emerged as a cultural nexus of power along with individuals who contributed to them to provide different types of welfare and social services to the community, which the colonial government in Hong Kong failed to provide.
Keywords: Protestant churches in Hong Kong; Chinese immigrants; Hong Kong history; social agents